The Fundamental Elements of the User Oriented Archival Services - Access - Şentürk, Burçak (Information World, 2011)
Archives are from past to present the institutions where materials should be preserved for various reasons. In such institutions the expectations of users were usually deemed to be of secondary importance and user orientation was not given due consideration. However, there are two constant and un-changing realities for archives: First, archives should be considered as service organizations because they provide user services. Secondly, irrespective of type, the focus of every organisation that offers a service should be its user/customer and archives should provide “User Oriented Archival Services“. Within this context, this study argues that the fundamental elements that user oriented archival services should aim for are: Access, research area, material and archivist. This study highlights the first element of the user oriented archival services which is access. In addition, the main steps of the user oriented access process and the specifications that it should possess are also analysed in this study.